Optical and electrical properties of electrochemically doped organic field effect transistors - Yumusak, Cigdem; Abbas, Mamatimin; Sariciftci, Niyazi Serdar (ELSEVIER, 2013)
Mixed ionic/electronic conduction in conducting polymers introduces new physics/chemistry and an additional functionality in organic optoelectronic devices. The incorporation of an ionic species in a conjugated polymer matrix results in the increase in electrical conductivity associated with the electrochemical doping of the material. In recent years polymer light emitting electrochemical cells (LECs) have been demonstrated. In such electrochemical optoelectronic devices, mobile ions facilitate the efficient injection of electronic charge carriers creating in situ doping regions near the electrodes and lead to efficient electroluminescence light emission. Here, we introduce the same concept of an LEC in the organic field effect transistors (OFETs). The presence of both electronic and ionic charge carriers in the active layers of OFETs brings high charge carrier mobility and light emission even using symmetric source and drain metal electrodes. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Organic light emitting transistor; Organic field effect transistor; Electrochemical transistor; Electrochemical light emitting transistor; Electrochemical doping; Organic electronics; LIGHT-EMITTING TRANSISTORS; THIN-FILM TRANSISTORS; OPTOELECTRONIC PROPERTIES; AMBIPOLAR; EMISSION; STATE; CONDUCTIVITY; GATE; POLYANILINE; TRANSPORT; Optics